Evacuation of sediments from reservoirs - White, W. R., Dr (Thomas Telford, 2001)
One method of removing sediments from reservoirs is flushing sediments through purpose-built outlet works within the dam. This can be applied to existing dams, with adaptation of the engineering works, and to new dams. The title covers hydraulic, hydrological, sedimentological and topographical features required for successful flushing.